Analyzing Purchasing Patterns of Agri-Food Commodities for Every State in Malaysia Using Association Rules - Bonaventure, Boniface; Geoffrey Harvey, Tanakinjal; Rayner, Alfred; Mori, Kogid; Stephen L., Sondoh; Assis, Kamu; Alesia Sigang, Gugkang; Anath Rau, Krishnan; Nalini, Arumugam; Nolila Mohd, Nawi; Venus Liew, Khim Sen; Harry, Entebang (2024)
Malaysia relies heavily on food imports, making it vulnerable to global market fluctuations and supply chain disruptions. Knowing which agri-food com-modities are often consumed together or have complementary markets can inform export strategies and boost the agricultural sector’s economic contribution. Market basket analysis can be used to provide valuable insights into the relationships between different items in a dataset and can be used for decision-making, recommendation systems, and optimizing business processes. The aim of this paper is to investigate the relationships between agri-food commodities in Malaysia for 13 states and 2 districts using Association rules, as it provides insights into consumer preferences and behavior. The datasets were collected from February 2022 through January 2023 from 13 states and 3 federal territories, which consists of 56,878 number of transactions recorded with 324 number of unique items. Based on the findings of this paper, it can be observed that the extracted rules for every state focuses on different types of agri-food commodities. These extracted rules can be applied for crop planning and production optimization, diversification of agricultural products, supply chain effficiency and local and sustainable agriculture activities. For future works, a more comprehensive validation works is recommended to be conducted to validate these extracted rules so that they can be applied by retailers in each state in Malaysia.